Doing Business 2012 : Doing Business in a More Transparent World. (Doing Business., 2012)
Ninth in a series of annual reports comparing businessregulations in 183 economies, Doing Business 2012 measuresregulations affecting 11 areas of everyday business activity: starting a business dealing with construction permits employing workers registering property getting credit protecting investors paying taxes trading across borders enforcing contracts closing a business getting electricity The report updates all indicators as of June 1, 2011, ranks countrieson their overall "ease of doing business", and analyzes reformsto business regulation-identifying which countriesare streng.